Dissociation and Combustion of a Layer of Methane Hydrate Powder: Ways to Increase the Efficiency of Combustion and Degassing - Sergey Y. Misyura; Igor G. Donskoy (Energies, 2021)
The interest in natural gas hydrates is due both to huge natural reserves and to the strengthened role of environmentally friendly energy sources conditioned by the deterioration of the global environmental situation. The combustion efficiency increase is associated with the development of understanding of both the processes of dissociation and combustion of gas hydrates. To date, the problems of dissociation and combustion have, as a rule, been considered separately, despite their close interrelation. Usually, during combustion, there is a predetermined methane flow from the powder surface. In the present paper, the combustion of methane hydrate is simulated taking into account the non-stationary dissociation process in the powder layer. Experimental studies on the methane hydrate dissociation at negative temperatures have been carried out. It is shown that due to the increase in the layer temperature and changes in the porosity of the layer over time, i.e., coalescence of particles, the thermal conductivity of the layer can change significantly, which affects the heat flux and the dissociation rate. The flame front velocity was measured at different external air velocities. The air velocity and the vapor concentration in the combustion zone are shown to strongly affect the combustion temperature, flame stability and the flame front velocity. The obtained results may be applied to increase the efficiency of burning of a layer of methane hydrate powder, as well as for technologies of degassing the combustible gases and their application in the energy sector.